THE EFFECT OF GREEN INNOVATION ON COMPANY SUSTAINABILITY PERFORMANCE WITH CEO TENURE AS A MODERATING VARIABLETHE EFFECT OF GREEN INNOVATION ON COMPANY SUSTAINABILITY PERFORMANCE WITH CEO TENURE AS A MODERATING VARIABLE - Arifin, Andi Harmoko (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine green innovation on company sustainability and whether there is a tenured CEO who plays a moderating role. This research uses a sampling method in the form of non-probability sampling. The sampling technique used in this research used purposive sampling. The analytical method used in this research is a quantitative analysis method. The results of this research show that green innovation has a significant effect on company sustainability. And the CEO is able to moderate green innovation towards company sustainability . Keywords: CEO Tenure. Company Sustainability, Green Innovation